Techno-Economic Impacts of Battery Replacement for Different EV Usage Patterns - Martin Chaud; Ronan German; Eric Hittinger; Alain Bouscayrol; Elodie Castex (IEEE Open Journal of Vehicular Technology, 2025)
The driving range of an electric vehicle is limited by the energy of the battery. It decreases over time due to ageing. The vehicle user can replace the battery after some operational period to restore the initial capacity. This paper studies the impact of battery replacements from the driving range and economic perspectives. A global vehicle model is defined. It considers the ageing, the economic value and the electro thermal model of the battery in interaction with the vehicle usage. A Renault Zoe is chosen as a reference vehicle. Three different usage scenarios are defined: low-intensity urban, medium-intensity rural and high-intensity motorway driving cycles for a 12-year vehicle lifespan. The results show that replacing the battery at least one time is necessary for high motorway daily usage. Frequently replacing the battery (every three years) has a positive impact on the driving range while increasing the battery cost of ownership. A high annual mileage can have more impact than battery replacements. User trade-offs between driving range and battery cost are presented.